The Theoretical Description for Fluoxetine Electrochemical Determination, Assisted by CoO(OH)-Nanoparticles, Deposited Over the Squaraine Dye - Tkach, Volodymyr V.; Kushnir, Marta V.; de Oliveira, Sílvio C.; Salomova, Hanifa Zh.; Jalilov, Fazliddin; Jalilova, Feruza; Musayeva, Dilfuza M.; Niyazov, Laziz N.; Ivanushko, Yana G.; Ahafonova, Oleksandra V.; Mytchenok, Maria P.; Yagodynets´Petro I.; et al. (Orbital: The Electronic Journal of Chemistry, 2021)
The theoretical description of the fluoxetine electrochemical determination over a CoO(OH) – Squaraine Dye composite has been carried out in this work. The correspondent mathematical model has been developed and analyzed by means of the linear stability theory and bifurcation analysis. It has been shown that the cobalt(III) oxyhydroxide, stabilized by squaraine dye layer, may be efficient electrode modifier for fluoxetine electrochemical determination. The possibility for the oscillatory and monotonic instabilities has also been verified. DOI: http://dx.doi.org/10.17807/orbital.v13i1.1573